2014
DOI: 10.1149/2.039405jes
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Plasma Exfoliated Vertically-Aligned Carbon Nanotubes as Electrodes for Ultrasensitive Stripping Detection of Pb2+

Abstract: In the present paper we report the production of vertically aligned carbon nanotubes exfoliated (at the tips) by oxygen plasma for electrochemical applications. The fast and dry process produces graphene oxide tips and oxygen functionalization. The electrodes are evaluated by cyclic voltametry by ferri/ferrocyanide redox couple and applied for electrochemical detection of lead (II) by differential pulsed anodic stripping voltammetry. The electrode presents high sensitivity (35.47 uA.uM −1 ) and low detection l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 85 publications
(94 reference statements)
0
6
0
Order By: Relevance
“…D* band is related to amorphous-like carbons (e.g., defectrich short carbon layers). The D # band is assigned to oxygen functional groups onto carbon surface such as C-O, C=O, COOas reported by us elsewhere (59)(60)(61)(62)(63). Therefore, we refer to D # as Carbon with functional oxygen group band, CfO.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 87%
“…D* band is related to amorphous-like carbons (e.g., defectrich short carbon layers). The D # band is assigned to oxygen functional groups onto carbon surface such as C-O, C=O, COOas reported by us elsewhere (59)(60)(61)(62)(63). Therefore, we refer to D # as Carbon with functional oxygen group band, CfO.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 87%
“…A comparison of these three cases demonstrates that the electrochemical DNA-based sensor is considerably helpful in detecting Pb 2+ with a higher ΔR ct value of 0.46 kohm. For the NH 2 -rGO sample, an interesting result showed a decrease in the R ct value after the plasma treatment, indicating that the electrochemical performance of rGO after plasma modification improved [23]. As discussed above, amino groups were produced on the NH 2 -rGO surface, further leading to electrostatic interaction between positively charged ammonium group and the negatively charged phosphate groups on single strand DNA in the aqueous solution [18].…”
Section: Basic Characterization Of Nh 2 -Rgomentioning
confidence: 91%
“…Saito et al 82 reported the application of a VACNT-GO electrode for the determination of lead (II). The electrode was initially evaluated by cyclic voltammetry using the electrochemical ferri/ferrocyanide redox couple.…”
Section: Electrochemical Sensors Based On Vacntmentioning
confidence: 99%